PEMBELAJARAN BAHASA INGGRIS III BERBASIS MIND MAP UNTUK MENINGKATKAN SKOR TOEFL MAHASISWA STMIK SINAR NUSANTARA - Sri Hariyati Fitriasih, Suryanti Galuh Pravitasari (PROSIDING, 2014)
Having a suitable and efective way of solving the problems on Part II of TOEFL test (StructureÂ and Error Identification) will surely give definite result on the studentsâ TOEFL score. To reachÂ this, it is necessary to apply a certain method or teaching technique that is good and fun evenÂ effective so that the students can understand the material faster and better. This study used trueexperimental design in which the students in the experimental class were taught using Mind MapÂ method in the teaching and learning process. The result of the post test is 426 for the averageÂ score of experiment class and 399 in control class. The result of the t-test is that the t-calculated-tÂ < t-table (0.239 < 1.984) and p value: 0.812 > 0.05. Therefore the hypothesis is proved to be truethat using Mind Map in teaching Bahasa Inggris III is proved to effectively increase the studentsâÂ TOEFL score.Keywords: effective, mind map, teaching and learning process